Alcohol expectancies in childhood: change with the onset of drinking and ability to predict adolescent drunkenness and binge drinking. (12th September 2014) - Jester, Jennifer M.; Wong, Maria M.; Cranford, James A.; Buu, Anne; Fitzgerald, Hiram E.; Zucker, Robert A.
Abstract Aims We examined the relationship between alcohol expectancies in childhood and onset of drinking, binge drinking and drunkenness in adolescence and the influence of drinking onset on expectancy development. Design A prospective, longitudinal study of children assessed for alcohol expectancies and drinking at four time‐points between ages 6 and 17 years. Setting Community study of families at high risk for alcoholism conducted in a four‐county area in the Midwestern United States. Participants The study involved 614 children; 460 were children of alcoholics and 70% were male. Measurements Expectancies about alcohol effects were measured using the Beverage Opinion Questionnaire and child's drinking by the Drinking and Drug History—Youth Form. Findings Partial factor invariance was found for expectancy factors from ages 6 to 17 years. Survival analysis showed that social/relaxation expectancies in childhood predicted time to onset of binge drinking and first time drunk (Wald χ2, 1 d.f. = 3.8, P = 0.05 and 5.0, P < 0.05, respectively). The reciprocal effect was also present; when adolescents began drinking, there was an increase in social/relaxation expectancy and a concomitant increase in slope of the expectancy changes lasting throughout adolescence. Conclusions A reciprocal relationship exists between childhood alcohol expectancies and the development of alcohol involvement. Higher expectancies for positive effects predict earlier onset of problem drinking. Onset of use, in turn, predicts an increase in rate of development of positive expectancies.